2019
DOI: 10.1177/0363546518819786
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Posterior Tibial Slope Does Not Affect Postoperative Posterior Knee Laxity After Double-Bundle Posterior Cruciate Ligament Reconstruction

Abstract: Background: Recent clinical studies have identified sagittal plane posterior tibial slope as a risk factor for increased postoperative laxity after single-bundle (SB) posterior cruciate ligament reconstruction (PCLR). However, the effect of tibial slope and its role in graft laxity following double-bundle (DB) PCLR has not been investigated clinically. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 23 publications
0
23
3
Order By: Relevance
“…9,33 Despite the findings from the current study and the supporting literature that lateral PTS likely has a greater effect on overall ACL strain than does medial PTS, several studies have shown that severe inclinations at either plateau can significantly affect overall ACL strain and that both the medial and lateral PTS likely affect ACL stability. 9,67 The current meta-analysis also provides accurate, updated normative values for 3 distinct cohorts based on ACL integrity: intact ACL, primary ACL tear, and failed ACLR. Specifically, for knee surgeons and sports medicine researchers, PTS is a growing area of interest and clinicians/researchers are often forced to reference larger case series when attempting to identify the average PTS of patients.…”
Section: Discussioncontrasting
confidence: 89%
“…9,33 Despite the findings from the current study and the supporting literature that lateral PTS likely has a greater effect on overall ACL strain than does medial PTS, several studies have shown that severe inclinations at either plateau can significantly affect overall ACL strain and that both the medial and lateral PTS likely affect ACL stability. 9,67 The current meta-analysis also provides accurate, updated normative values for 3 distinct cohorts based on ACL integrity: intact ACL, primary ACL tear, and failed ACLR. Specifically, for knee surgeons and sports medicine researchers, PTS is a growing area of interest and clinicians/researchers are often forced to reference larger case series when attempting to identify the average PTS of patients.…”
Section: Discussioncontrasting
confidence: 89%
“…In the first of these, 3 the authors report that the posterior tibial slope in 104 PCL-injured knees averaged almost 3° less than that in a matched group of controls without ligament injury. In the second study, 2 the authors examine the results of PCL reconstruction through the lens of tibial slope. They report that their double-bundle technique successfully reduced the mean side-to-side difference in posterior tibial translation from 10.6 to 1.5 mm as measured in stress radiographs obtained 18.5 months after surgery.…”
mentioning
confidence: 99%
“…Biomechanical studies have shown that a decrease in the posterior tibial slope can increase the PCL graft force 4 and the PTT in the PCL-deficient knee under a posterior drawer. 10 , 34 However, it is controversial in clinical settings; Bernhardson et al 5 demonstrated that the postoperative PTT was not influenced by a decreased posterior tibial slope after double-bundle PCLR at 18.5 months postoperatively. Conversely, in a single linear regression analysis after single-bundle PCLR, Gwinner et al 12 showed that the flattening of the posterior tibial slope was associated with a significantly greater persistent PTT at a longer follow-up point of 103 months, where sex and the number of operated ligaments were not considered.…”
Section: Discussionmentioning
confidence: 99%
“…The mean posterior tibial slope in the current study was 6.8° ± 2.3° (range, 3.0°-13.0°) and was pretty much average compared with the previous data (from 5.9° to 8.0°). 5 , 12 This could indicate that only extreme flattening of the posterior tibial slope affected the PTT. However, future studies might be warranted to investigate the effect of the posterior tibial slope after double-bundle PCLR with a longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation